2014
DOI: 10.1080/13573322.2014.881337
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the impact of the London 2012 Olympics on families in the East Midlands of England: lessons for sports development policy and practice

Abstract: The dynamics and culture of families are central to individual and community sport and physical activity participation. This research project examined the lived experiences and dayto-day realities of the London 2012 Olympics from the perspectives of five families in the East Midlands region of England. The aims of the project were to assess the influence the Games had on shaping family sports participation, influencing social and health relationships within the families through sports and reactions to the 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
1
24
0
2
Order By: Relevance
“…Such subtle differences may be critical in developing relationships between faith communities and sport development practitioners aiming to increase participation levels. It also illustrates the importance of recognising complexity of locally negotiated aspects of identity in determining behaviour in response to government sport development policy (Mackintosh et al, 2015;Hylton and Morpeth, 2014). Sometimes this stands in contrast to pleas for more national 'insight' and campaigns and products to shape participation in national sport development policy (HM Government, 2015;Sport England, 2016a).…”
Section: Islamic Religious Identities and Their Multiple Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Such subtle differences may be critical in developing relationships between faith communities and sport development practitioners aiming to increase participation levels. It also illustrates the importance of recognising complexity of locally negotiated aspects of identity in determining behaviour in response to government sport development policy (Mackintosh et al, 2015;Hylton and Morpeth, 2014). Sometimes this stands in contrast to pleas for more national 'insight' and campaigns and products to shape participation in national sport development policy (HM Government, 2015;Sport England, 2016a).…”
Section: Islamic Religious Identities and Their Multiple Relationshipmentioning
confidence: 99%
“…This is contrasted with Kahan (2003) who states that traditional Muslim families instruct their children to follow their path, which causes them to frown upon sport as an impediment to achieving education and career goals. This critical nexus between family, sporting interests and Islamic faith factors is at the heart of uncovering the 'participation puzzle' so many policy makers currently seek to address (Mackintosh et al, 2015;Girginov and Hills, 2008).…”
Section: Islamic Religious Identities and Their Multiple Relationshipmentioning
confidence: 99%
“…A group of studies have specifically examined youth engagement with the Olympics (Cotton, 2012;Griffiths and Armour, 2013;Johnson et al, 2008;Kohe and Bowen-Jones, 2016;Reis et al, 2014). Focusing on the London 2012 Olympic Games, the work of Cotton (2012), Griffiths and Armour (2013), Kohe and Bowen-Jones (2016) and of Mackintosh et al (2015), are all particularly useful. Written before the London 2012 Olympic Games, Cotton's small-scale qualitative study revealed that, although the event may have been able to inspire young people to take up sports, the Olympic Games' association with certain Olympic sponsors (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qualitative research examining the London 2012 Olympics and its impact on sports participation in the UK is minimal (Mackintosh et al, 2014). The studies that exist, have analysed the build-up to the Games and the plans to deliver the participation legacy.…”
Section: Introductionmentioning
confidence: 99%
“…The Government department for sport's policy document Creating a Sporting Habit for Life (2012) established a vision of a positive future 2012 legacy and an upwards trajectory of sports participation (Mackintosh et al, 2014). However, the success of this legacy has been criticised because sports participation 1 figures of regular involvement 2 , amongst young people (16 to 25-yearolds) and adults (over 26 years) have dropped since the Games (Sport England, Active People 1 Participation in 30 minutes of moderate intensity sport.…”
Section: Introductionmentioning
confidence: 99%